2021
DOI: 10.1080/08974438.2021.1889733
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance of Insects as Food: Revision of Food Neophobia Scales

Abstract: Please refer to any applicable terms of use of the publisher DOI link to the version of record on the publisher's site 1 Consumer acceptance of insects as food: Revision of food neophobia scalesThis study aimed to get insight into the acceptance of insects as food using neophobia descriptors. Data were collected through questionnaires applied to a Spanish-Dominican sample. Models were created using binary logistic regression, and determinants of acceptance of insects as food were obtained. The results reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…From the studies included in the review, twenty-five were cross-sectional studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. All cross-sectional studies were supported on questionnaire surveys, while the qualitative studies were based on focus groups (five studies) [ 57 , 58 , 59 , 60 , 61 ] and interviews (one study) [ 62 ] as methodologies for data collection ( Table A1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the studies included in the review, twenty-five were cross-sectional studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. All cross-sectional studies were supported on questionnaire surveys, while the qualitative studies were based on focus groups (five studies) [ 57 , 58 , 59 , 60 , 61 ] and interviews (one study) [ 62 ] as methodologies for data collection ( Table A1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, addressing the main determinants that negatively affect the consumption of EI ( Table A1 ), it was observed that they are related with some sociodemographic characteristics such as age [ 24 , 53 ], gender (females) [ 53 ], living environment (rural areas) [ 53 ] and occupation (students) [ 53 ] as well as with sensory attributes such as appearance [ 18 , 43 , 46 , 57 ], odor [ 57 ], taste [ 43 , 57 ] and presentation mode (whole insects) [ 45 ]. Some other factors that also negatively influence EI consumption are related to tradition/culture [ 19 , 44 , 46 , 57 , 58 ], social influence [ 57 ], country of origin [ 42 ], lack of familiarity/past experience [ 53 , 58 ], religion [ 23 ], safety [ 18 , 19 , 41 , 46 ], risks [ 23 ], poor supply [ 46 ], seasonality [ 46 ], price [ 52 ], lack of knowledge [ 44 , 46 , 58 ], animal suffering [ 23 ], food neophobia [ 17 , 20 , 24 , 41 , 44 , 47 , 50 ], disgust [ 19 , 20 , 23 , 41 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A weblink to the questionnaire was sent via e-mail to in-country contacts who were responsible for distributing it among pre-existing contact lists, which yielded most of the responses. Social media platforms such as LinkedIn were also used [ 18 , 19 ]. All data was collected, collated and centrally stored at the Harper Adams University server in the UK.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire also contained the statements of The Food Neophobia Scale (FNS). The FNS is a tested and validated scale to measure reluctance to engage with novel foods [ 19 , 22 ]. It consists of five neophiliac statements and five neophobic questions.…”
Section: Methodsmentioning
confidence: 99%